Mn(III)-Mediated Facile Access to Polysubstituted α-Naphthols from β-Keto Ester Derivatives and Terminal Alkynes - He, Lisheng; Yang, Yuzhu; Li, Fei; Liu, Xiaolan; Pan, Weidong (Synthesis, 2020)
A novel manganese-mediated reaction for the synthesis of polysubstituted α-naphthols has been developed from β-keto esters and terminal alkynes. This system holds the advantages of readily available starting materials and mild conditions. Mechanistic investigations revealed that this reaction proceeds via a tandem radical cyclization process.
Keywords: α-naphthols; manganese; terminal alkynes; radical process; mild conditions